1982
DOI: 10.1002/food.19820260405
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of the current studies on pangamic acid ‐ vitamin B15

Abstract: The research on pangamic acid (vitamin B15) has been conducted by specialists in many fields of science for along time. This, however, has not put an end to controversies around the problem of its therapeutic effect. The solution to the basic problems, i.e. defining the compound structure, finding an explicit method of its determination and identification as well as the evidence of its biochemical and physiological functions in the human organism appears as distant as ever. It has been found out, however, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other authors estimate PA as scientifically untenable [2] or as a "fake-vitamin" [6]. Independent of the valid status of PA and whether it exists in reality or not, it seems that defining the compound's structure and physiological functions in the human organism appears as distant as ever [7]. These authors also quote that it has been found out, however, that either some preparations referred to as pangamic acid or their components may be detrimental to man's health.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors estimate PA as scientifically untenable [2] or as a "fake-vitamin" [6]. Independent of the valid status of PA and whether it exists in reality or not, it seems that defining the compound's structure and physiological functions in the human organism appears as distant as ever [7]. These authors also quote that it has been found out, however, that either some preparations referred to as pangamic acid or their components may be detrimental to man's health.…”
Section: Introductionmentioning
confidence: 99%